FUZZY TECHNIQUES FOR ACCESS AND DATA MANAGEMENT IN HOME AUTOMATION ENVIRONMENTS - COLLOTTA, MARIO; CONTI, VINCENZO; PAU, GIOVANNI; SCATA, GIANFRANCO; VITABILE, SALVATORE (Journal of Mobile Multimedia, 2012)
Home Automation Environments are characterized by the integration of electronic devices as well as by the performance of communication and control systems. Environment infrastructure has to meet several requirements including Quality of Service (QoS), safety, security, and energy saving. However, Home Automation deals with complex environments, so that advanced data management systems are required to meet the above constraints. Fuzzy Logic based techniques can be successful used to improve system performance management. This work proposes and describes the use and application of fuzzy rules on a two-tiered architecture integrating a biometric authentication module and communication real-time constraints. The goal is to combine the advantages of wired and wireless networks as well as the biometric recognition accuracy to increase the flexibility and the performance of the proposed deadline oriented architecture. The experimental results of the user authentication module, the energy consumption module and the scheduling module for real-time mobile communication are also outlined.